Undenatured type II collagen mitigates inflammation and cartilage degeneration in healthy Labrador Retrievers during an exercise regimen. Issue 2 (10th May 2021) - Varney, J L; Fowler, J W; Coon, C N
Abstract: The aim of this experiment was to evaluate the effect of undenatured type II collagen supplementation on inflammation and cartilage degeneration after exercise in healthy dogs. Forty healthy Labrador Retrievers (20 male/20 female; range 5-12 yr; average 8 yr) were sorted into two groups: undenatured type II collagen group receiving 40 mg UC-II (10 mg collagen type II/min. 3% undenatured type II collagen; Lonza Consumer Health, Inc.) and placebo group receiving 40 mg maltodextrin daily by capsule. After 2-wk loading, all dogs began an 11-wk endurance exercise regimen consisting of two weekly runs, starting at 5 km and increasing incrementally to 8 km, with one final 16 km run. Blood samples were collected at baseline, pre and post first 5 km run, and pre- and post-16 km run. Activity per kilometer was greater in male undenatured type II collagen vs. male placebo over all runs ( P = 0.004), and average moving speed was greater in all undenatured type II collagen dogs compared with placebo over all runs ( P < 0.001). Hematology analysis indicated that during the first insult, undenatured type II collagen dogs had a greater lymphocyte count ( P < 0.001) and lymphocyte percentage ( P = 0.001) vs. placebo dogs. Undenatured type II collagen dogs had a lesser neutrophil percentage ( P = 0.042) and neutrophil to lymphocyte ratios ( P = 0.001) compared to placebo dogs. For the final insult, undenatured type II collagen dogs had greater lymphocyte percentage ( P = 0.013) and lesser mean corpuscular hemoglobin concentration ( P = 0.043) compared with placebo dogs. Both groups had significant changes between timepoints for several hematological parameters. Biomarker IL-6 was lesser in undenatured type II collagen dogs compared with placebo at post 5 km ( P = 0.037). Cartilage oligomeric matrix protein (COMP) was lesser in undenatured type II collagen dogs at post 16 km ( P = 0.023), and only the placebo dogs had a significant increase in COMP from pre to post 16 km ( P = 0.021). In summary, Labrador Retrievers supplemented with undenatured type II collagen had decreased inflammation and cartilage degeneration compared with nonsupplemented dogs during exercise.